Elevated CO2 Did Not Stimulate Stem Growth in 11 Provenances of a Globally Important Hardwood Plantation Species - Wesolowski, Anita; Blackman, Chris J.; Smith, Renee A.; Tissue, David T.; Pfautsch, Sebastian (Frontiers in Forests and Global Change, 2020)
Elevated atmospheric carbon dioxide (eCO2) often enhances rates of photosynthesis leading to increased productivity in trees. In their native habitats in Australia, eucalypts display considerable phenotypic plasticity in response to changes in environmental conditions. Little is known whether this plasticity can be harnessed effectively under future atmospheric eCO2 conditions and be used to identify provenances with superior growth. Here, we report two experiments that assessed the physiological and growth responses of Eucalyptus grandis – one of the world’s most important hardwood plantation species – to eCO2. We used 11 provenances from contrasting climates. Our selection was based on site-specific information of long-term temperature and water availability. In Experiment 1, four provenances exhibited significant variation in light-saturated photosynthetic rates (Asat), stomatal conductance (gs) and concentrations of non-structural carbohydrates in leaves, stems and roots when grown under ambient CO2 (aCO2). Biomass of leaves, stems and roots varied significantly and were negatively correlated with mean annual temperature (MAT) at seed origin, indicating that provenances from cooler, wetter climates generally produced greater biomass. Yet, stem growth of these provenances was not stimulated by eCO2. Given the vast environmental gradient covered by provenances of E. grandis, we expanded the selection from four to nine provenances in Experiment 2. This allowed us to validate results from Experiment 1 with its small selection and detailed measurements of various physiological parameters by focusing on growth responses to eCO2 across a wider environmental gradient in Experiment 2. In Experiment 2, nine provenances also exhibited intraspecific differences in growth, but these were not related to climate of origin, and eCO2 had little effect on growth traits. Growth responses under eCO2 varied widely across provenances in both experiments, confirming phenotypic plasticity in E. grandis, though responses were not systematically correlated with climate of origin. These results indicate that selection of provenances for improved stem growth of E. grandis under future eCO2 cannot be based solely on climate of origin, as is common practice for other planted tree species.